Ctenophores from the Oaxaca coast, including a checklist of species from the Pacific coast of Mexico - Ruiz-Escobar, Fernando; Valadez-Vargas, Diana K.; Oliveira, Otto M. P. (Zootaxa, 2015)
Ctenophores are poorly known in the tropical eastern Pacific, including the southern coast of Mexico. Previous records of ctenophores along the Pacific coast have been provided mainly from northern waters. For the coast of Oaxaca state, their occurrence has only been mentioned before at phylum level. In this paper, we provide the first three records of ctenophores for the Oaxacan coast, which represent new records of Beroe forskalii and Bolinopsis vitrea as well as the first record of Ocyropsis maculata in the tropical eastern Pacific. Descriptions of these three species, as well as a checklist of the ctenophores from the west coast of Mexico are provided.